2016
DOI: 10.1038/srep21832
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of N-doped graphene with high Curie temperature

Abstract: N-doped graphene with Curie temperature higher than room temperature is a good candidate for nanomagnetic applications. Here we report a kind of N-doped graphene that exhibits ferromagnetic property with high Curie temperature (>600 K). Four graphene samples were prepared through self-propagating high-temperature synthesis (SHS), and the doped nitrogen contents of in the samples were 0 at.%, 2.53 at.%, 9.21 at.% and 11.17 at.%. It has been found that the saturation magnetization and coercive field increase wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 68 publications
2
63
0
1
Order By: Relevance
“…There have been very few experimental work on magnetism in 2D materials . Difficulty in growing high‐quality samples is an issue.…”
Section: Spin Generationmentioning
confidence: 99%
“…There have been very few experimental work on magnetism in 2D materials . Difficulty in growing high‐quality samples is an issue.…”
Section: Spin Generationmentioning
confidence: 99%
“…209 Recently, N-G produced via self-propagating high-temperature synthesis (SHS) showed ferromagnetic properties at a high Curie temperature. 210 Some studies of edge doping of graphene via N atoms have also reported spin polarization and magnetic moments in graphene. 211 Doped graphene nanoribbon edges showed different ranges of magnetic moment depending on the N-doping sites; moreover, N-doped graphene nanoribbons with translational grain boundaries revealed spin-polarized ferromagnetic ordering.…”
Section: Substitution Of Group Va Elements In Graphenementioning
confidence: 99%
“…Therefore, despite its challenges, doping with n‐ or p‐type heteroatoms may be the most practical way to equip graphene with localized spins while maintaining a charge carrier concentration high enough to preserve its conductivity. In this context, nitrogen doping is envisioned as a method to imprint active centers into graphene to create materials suitable for organic‐based spintronics . Błoński et al recently reported that ferromagnetic spin ordering emerges in graphene doped with graphitic nitrogen.…”
mentioning
confidence: 99%